Prarancangan Pabrik Etanolamin Dari Etilen Oksida Dan AmoniakKapasitas 114.000 Ton/Tahun - Nugroho, Yunianto Tri; , Muhammad Mujiburohman, S.T., M.T., Ph.D; , Ir. Nur Hidayati, M.T., Ph.D (2017)
Ethanolamine factory with raw materials of ethylene oxide and ammonia is planned to be established at industrial zones in Cilegon, Banten, with a production capacity of 114,000 tonnes/year by 2020. The production of ethanolamine is carried out in a plug flow reactor operatednon-isothermally. Thermodynamically the reaction is irreversible and othermic. The reaction undergoes at a temperature range of (52-55)° C, and pressure of 3 atm. The plant needs etylene oxide as much as 11363.636 kg/hour and ammonia as much as 4393.11 kg/hour. The products consist of monoetanolamin as much as 7637.4289 kg/hour, diethanolamine as much as 5037.7793 kg/hour, and triethanolamine as much as 1839.6985 kg/hour. The support utilities includes water supply as much as 283,087.186 kg/h obtained from Cidanau river, steam demand as much as 52462.957 kg/h produced from the boiler with oil fuel as much as 1.13 m3/h. The need of compressed air is 500 kg/h and the electricity is supplied from the PLN supported a generator of 450 kW with usingg fuel as much as 0.0591 m3/h. The plant is operated for 330 days a year, and employs 120 people with a fixed capital of Rp506,955,694,146.00 per year, and working capital of Rp2.325.115.108.959.00 per year. The profit after tax can reach to Rp179,916,025,765.00 per year. The Return on Investment (ROI) before tax is 44.36% and 35.49% after tax. The Pay Out Time (POT) before tax is 1.82 years and 2.2 years after tax. The Break Even Point (BEP) is 40.27%, the Shut Down Point (SDP) is 24.16%, and the Internal Rate of Return (IRR) is 39.3%. Considering these economical parameters, where high risk parameters are fulfilled the plant is feasible to set up.